An Investigation of Casein Polymorphism in Sheep Milk - Adhikari, Alka; Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
Casein polymorphism in the milk of Indian Bikaneri sheep was investigated. 59.09% of casein α-F-types, 9.09% of casein α-S-types and 31.82% of casein α-SF-types were observed.